The Training of The Use of Finale Software in Songs Notation for Cultural Teachers of SMP In Pontianak - Imam Ghozali (Universitas Tanjungpura, 2019)
This Community Service (PKM) activity is motivated by the lack of knowledge and skills of most art and culture teachers in writing music notation with beam notation in junior high schools in Pontianak. Thus we need a media that can help accelerate and exact the understanding and skills of writing music notation. The method used is the implementation of the final program in the form of training and mentoring to increase interest, knowledge, and skills in writing block notation. The training is delivered in a variety of ways through lectures, demonstrations, questions and answers, and practices at MGMP (Subject Teachers' Group) teacher group meetings. The results of the activities show that the training program has achieved the expected objectives, namely increasing the interest, knowledge, and skills of teachers in writing block notation with finale media. It is indicated by the teacher's response to the activity, the results of the assignment, and the final test for writing simple songs.